EVALUATION OF PUBLIC STREET LIGHTING IN TANJUNGPURA UNIVERSITY ENVIRONMENT - Dirgantoro, Katon Sigit; Danial, Danial; Arsyad, Muhammad Iqbal (Faculty of Engineering, Universitas Tanjungpura, 2024)
Public Street Lighting (PJU) is a means used to improve the function of the road so that it can illuminate the road at night, improve safety, security, traffic comfort and make road users more comfortable in the campus environment. PJU lights in the Tanjungpura University environment already exist on Jalan Prof. Dr. H. Hadari Nawawi, especially around Tanjungpura University Currently, these lights use 250 watt SON lamps with a pole height of ± 9m and produce an average light intensity of 2188.38 cd with a light intensity of 16.69 lux. The average energy consumption per day is ± 170 kW, but the lighting intensity is not in accordance with SNI standards. The recommended improvement effort is to replace them with 120 watt LED lamps, which can meet SNI standards for secondary collector road classes with an illumination intensity of 3-7 lux. Evaluation and recommendations are needed to improve lighting conditions in the neighborhood. After being replaced with 120 watt LED lights, the average pole height is ± 9m, the light intensity is 954.52 cd, and the illumination intensity is 7,28 lux, the results meet the SNI standards for secondary collector road classes. Although the monthly electrical energy consumption reaches Rp.4,721,640, LED lights produce a clearer contrast of light on objects, although the intensity is lower than SON lamps which have a greater intensity, but the color and contrast on objects become clearer